The influence of transmedia and extra-academic narratives on the formation of the historical culture of high school students - Muñoz-Muñoz, Pablo; Ortuno-Molina, Jorge; Molina-Puche, Sebastian (Frontiers in Education, 2024)
This paper concerns with the importance of traditional and extra-academic sources of knowledge in the configuration of historical culture of Spanish adolescents. To conduct the research, a descriptive phenomenological approach has been designed by analyzing the responses of forty-eight students to a semi-structured interview in which they had to choose 5 characters of contemporary history and indicate the origin of the information. The results show the high coincidence of characters and the type of personalities chosen, also with high similarities in other studies conducted in Spain and other countries of the near sociocultural context. Although informal sources in the historical education of students is a clear fact, nevertheless it is still the formal context which has the greatest impact on adolescents. Therefore, the role of history teaching in schools provides a reinforcement of cultural values much more than to use historical knowledge as a tool of improvement of critical thinking, something that would be desirable to face the new challenges that multicultural societies imply.